2015
DOI: 10.5194/hess-19-91-2015
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution global topographic index values for use in large-scale hydrological modelling

Abstract: Abstract. Modelling land surface water flow is of critical importance for simulating land surface fluxes, predicting runoff and water table dynamics and for many other applications of Land Surface Models. Many approaches are based on the popular hydrology model TOPMODEL (TOPography-based hydrological MODEL), and the most important parameter of this model is the well-known topographic index. Here we present new, high-resolution parameter maps of the topographic index for all ice-free land pixels calculated from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 56 publications
1
80
0
1
Order By: Relevance
“…The comparison between HydroSHEDS and GMTED also indicated that, for capturing inundated areas under the same spatial resolution, the parameter maps derived from DEM without hydrological corrections have less accuracy compared to corrected ones (Lehner and Grill, 2013). Without hydrological corrections, valleys would appear as closed depressions in the DEM, leading to an underestimation of inundated areas (Marthews et al, 2015). It could be foreseen that if DEMs in process-based models are being applied at higher resolution, this drawback could be amplified.…”
Section: Cti Parameterizationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The comparison between HydroSHEDS and GMTED also indicated that, for capturing inundated areas under the same spatial resolution, the parameter maps derived from DEM without hydrological corrections have less accuracy compared to corrected ones (Lehner and Grill, 2013). Without hydrological corrections, valleys would appear as closed depressions in the DEM, leading to an underestimation of inundated areas (Marthews et al, 2015). It could be foreseen that if DEMs in process-based models are being applied at higher resolution, this drawback could be amplified.…”
Section: Cti Parameterizationsmentioning
confidence: 99%
“…As a result, it might underestimate the wetland areas within each grid cell and slightly underestimate the temporal pattern of saturated areas because of improper estimates of parameter C s (Güntner et al, 2004). One limitation of HydroSHEDS is that its projection is not equal-area like HYDRO1k (Marthews et al, 2015) and will cause a potential bias in slope calculation along east-west directions at high latitudes. However, since there is no common method to calculate slope or flow direction, we believe that our calculations provide a reasonable approximation for global applications.…”
Section: Cti Parameterizationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The topographic index λ has been calculated for Great Britain at 50 m 2 resolution from the CEH-IHDTM database (Morris and Flavin, 1990;1994), following the methodology in Marthews et al (2015), and then its mean and standard deviation at the 1 km 2 model grid are used as input data for the TOPMODEL approach.…”
Section: Ancillary and Driving Data 10mentioning
confidence: 99%